Peer review in an Era of Evaluation Understanding the Practice of Gatekeeping in Academia - Forsberg, Eva; Geschwind, Lars; Levander, Sara; Wermke, Wieland (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XIX, 402 p. 19 illus.